IEEE 2002 International Symposium on Technology and Society (ISTAS'02). Social Implications of Information and Communication Te
DOI: 10.1109/istas.2002.1013826
|View full text |Cite
|
Sign up to set email alerts
|

Improving Web-based civic information access: a case study of the 50 US states

Abstract: An analysis of the home pages of all fifty U. S. states reveals great variety in key design features that influence efficacy. Some states had excessively large byte counts that would slow users connected by commonly-used 56K modems. Many web sites had low numbers of or poorly organized links that would make it hard for citizens to find what they were interested in. Features such as search boxes, privacy policies, online help, or contact information need to be added by several states. Our analysis concludes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Researchers have investigated the accessibility of websites in the USA [1][2][3][4], UK [5], Australia [6], and Korea [7]. Some other researchers have evaluated web accessibility worldwide [8,9] or compared the accessibility of different kinds of websites [10].…”
Section: Web Accessibility Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have investigated the accessibility of websites in the USA [1][2][3][4], UK [5], Australia [6], and Korea [7]. Some other researchers have evaluated web accessibility worldwide [8,9] or compared the accessibility of different kinds of websites [10].…”
Section: Web Accessibility Evaluationmentioning
confidence: 99%
“…Given the fact that many websites fail to achieve web accessibility, a phenomenon that has been widely revealed by many researchers [1][2][3][4][5][6][7][8][9][10][11][12], there is likelihood that Chinese websites may have major accessibility problems; however, there is a lack of research into the accessibility of Chinese websites. This paper thus aims to provide an overview of the status of web accessibility in China according to two evaluations, one in 2009 and the other in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The state government sites were examined to determine if they had a statement addressing the accessibility of their Web sites [5]. Only 19 out of 50 states included a statement about the accessibility of their Web sites [5].…”
Section: Previous Researchmentioning
confidence: 99%
“…The state government sites were examined to determine if they had a statement addressing the accessibility of their Web sites [5]. Only 19 out of 50 states included a statement about the accessibility of their Web sites [5]. While the sites in that study were not examined for accessibility problems, it is quite likely that many of the other sites had not even considered accessibility as an issue.…”
Section: Previous Researchmentioning
confidence: 99%
“…Recent research has found that large percentages (70-98%, depending on the category of site) of web sites are not accessible. For instance, in recent studies, private and non-profit web sites [5], forprofit commerce web sites [12], U.S. state web sites [1], and even U.S. Federal web sites [11] were found to have major accessibility problems.…”
Section: Introductionmentioning
confidence: 99%